Predictably irrational : the hidden forces that shape our decisions - Ariely, Dan. (New York : Harper Perennial, 2010)
Why do smart people make irrational decisions every day? The answers will surprise you. This book is a look at why we all make illogical decisions. Why can a 50-cent aspirin do what a penny aspirin can't? If an item is "free" it must be a bargain, right? Why is everything relative, even when it shouldn't be? How do our expectations influence our actual opinions and decisions? In this book, the author, a behavioral economist cuts to the heart of our strange behaviour, demonstrating how irrationality often supplants rational thought and that the reason for this is embedded in the very structure of our minds. This book blends everyday experiences with a series of illuminating and often surprising experiments, that will change the understanding of human behaviour. And, by recognizing these patterns, the author shows that we can make better decisions in business, in matters of collective welfare, and in our everyday lives from drinking coffee to losing weight, buying a car to choosing a romantic partner.
How an injury led me to irrationality and to the research described here -- The truth about relativity: why everything is relative, even when it shouldn't be -- The fallacy of supply and demand: why the price of pearls and everything else is up in the air -- The cost of zero cost: why we often pay too much when we pay nothing -- The cost of social norms: why we are happy to do things, but not when we are paid to do them -- The power of a free cookie: how free can make us less selfish -- The influence of arousal: why hot is much hotter than we realize -- The problem of procrastination and self-control: why we can't make ourselves do what we want to do -- The high price of ownership: why we overvalue what we have -- Keeping doors open: why options distract us from our main objective -- The effect of expectations: why the mind gets what it expects -- The power of price: why a 50 cent aspirin can do what a penny aspirin can't -- The cycle of distrust: why we don't believe what marketers tell us -- The context of our character part I: why we are dishonest, and what we can do about it -- The context of our character, part II: why dealing with cash makes us more honest -- Beer and free lunches: what is behavioral economics and where are the free lunches?
"Revised and expanded edition."
Includes bibliographical references (pages 335-349).
Keywords: Decision making; Reasoning (Psychology); Economics -- Psychological aspects; Judgment; Consumer behavior